Sulodexide for limb salvage in refractory diabetic foot ulcer with arteriosclerosis obliterans: a case report - Chen, Zhaoyan; Lin, Wei (Frontiers in Endocrinology, 2026)
BackgroundPatients with diabetic foot ulcers (DFU) remain at substantial risk for impaired wound healing, even following successful revascularization. This clinical challenge is often associated with underlying microcirculatory dysfunction, highlighting a critical unmet need for effective intervention strategies.Case descriptionA 77-year-old female patient was suffering from severe DFU on her right foot, with infected wound, complicated by arteriosclerosis obliterans of the lower limbs. She underwent surgical debridement and angiographically and hemodynamically successful endovascular angioplasty. Despite these interventions and restored macrovascular perfusion, the wound exhibited continuously deterioration, and the patient was at imminent risk of minor amputation. Therefore, persistent microcirculatory dysfunction was considered a major contributing factor to the poor healing response, prompting the initiation of a salvage regimen with intravenous Sulodexide (600 LSU/day). Following a 51-day Sulodexide treatment, complete wound healing was achieved and the patient was discharged.ConclusionThis case report suggests that highly selected DFU patients unresponsive to standard therapies including successful revascularization, Sulodexide may be a plausible salvage or adjunctive therapeutic option. This observation is strictly hypothesis-generating and its potential role warrants investigation in future prospective clinical trials.